Forms and Models of Gender-Based Inclusive Leadership at the Service-Based Ponorogo State Islamic Institute (IAIN) through an analysis of the Big Five Personality Treatment - Ghafar, Muhammad; Imtihanah , Anis Hidayatul (Universitas KH. A. Wahab Hasbullah, 2025)
This article aims to describe the form and model of gender-based inclusive leadership at the Ponorogo State Islamic Institute Based on Service through the analysis of the Big Five Personality Treatment. This study uses a qualitative approach with a case study research type. Data collection techniques used are unstructured in-depth interviews, participant observation, and documentation. Data analysis was carried out during the research process and afterward through data reduction, data presentation, and drawing conclusions (verification). Data validity tests in this study include credibility, dependency, and confirmability tests. The results of the study are in the form of a pyramid with three levels of management, 1) top management, 2) middle management, and 3) staff management. Where the Rector as top management sets the goals and policies of IAIN Ponorogo through efforts to establish internal quality assurance standards. Middle management plays a role in developing human resources by clarifying tasks in each work unit. Staff management plays a role in good basic services. The characteristics of successful female leadership profiles at IAIN Ponorogo are shown by communication behavior in a relaxed atmosphere, open thinking in academic administration, maintaining personal relationships between lecturers and students, maintaining emotional stability of the academic community, team collaboration and mentoring, and increasing team motivation in realizing competitiveness targets. Keywords: Inclusive leadership; gender; Service; Big Five Personalities. ABSTRAK Artikel ini bertujuan untuk mendeskripsikan bentuk dan model kepemimpinan inklusif berbasis gender di Institut Agama Islam Negeri Ponorogo Berbasis Pelayanan melalui analisis Perlakuan Kepribadian Lima Besar. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Teknik pengumpulan data yang digunakan adalah wawancara mendalam tidak terstruktur, observasi partisipatif, dan dokumentasi. Analisis data dilakukan selama proses penelitian dan sesudahnya melalui reduksi data, penyajian data, dan penarikan kesimpulan (verifikasi). Uji keabsahan data dalam penelitian ini meliputi uji kredibilitas, dependabilitas, dan konfirmabilitas. Hasil penelitian yaitu bentuk piramida dengan tiga tingkatan manajemen, 1) manajemen puncak, 2) manajemen madya, dan 3) manajemen staf. Dimana Rektor sebagai manajemen puncak menetapkan tujuan dan kebijakan IAIN Ponorogo melalui upaya penetapan standar penjaminan mutu internal. Manajemen madya berperan dalam pengembangan sumber daya manusia dengan memperjelas tugas pada setiap unit kerja. Manajemen staf berperan dalam pelayanan dasar yang baik. Ciri-ciri profil kepemimpinan perempuan yang sukses di IAIN Ponorogo ditunjukkan dengan perilaku komunikasi dalam suasana santai, berpikir terbuka dalam administrasi akademik, menjaga hubungan personal antara dosen dan mahasiswa, menjaga kestabilan emosional civitas akademika, kolaborasi dan mentoring tim, meningkatkan motivasi tim dalam mewujudkan target daya saing. Kata Kunci: Kepemimpinan inklusif; gender; pelayanan; lima kepribadian besar.